Design of a multi-sensor platform for integrating extracellular acidification rate with multi-metabolite flux measurement for small biological samples - Obeidat, Yusra M., author; Chen, Tom, advisor; Pasricha, Sudeep, committee member; Collins, George, committee member; Tobet, Stuart, committee member (Colorado State University. Libraries, 2019)
To view the abstract, please see the full text of the document.